Peran Dinas Sosial dalam Penertiban Gelandangan dan Pengemis di Kota Surakarta - Agustin Mega Prastiwi; Waluyo Waluyo; Fatma Ulfatun Najicha (Jurnal Discretie, 2022)
This legal research describes and examine two problems. First, how sosial service take action in put in order homeless and beggars according to government rules number 31 year 1980, about countermeasures homeless and beggars in Surakarta city in put in order homeless and beggars. Second, which hinders factors that made Surakarta Social Services (Dinas Sosial Surakarta) in put in order homeless and beggars. This research is normative legal research with prescriptive character and using statutes approach. Legal material primary source is the legislation rule and legal material secondary source are books, article journals, science article, and interviews. This research using silogisme methods with deductive mind patterns with collection technique materials are using study documents and interviews. The purpose from this research consists of two purpose which are subjective and objective. Based on the results of this study, it can be conclude that the role of the Surakarta Social Service in an effort to put in order homeless and beggars under government regulations number 31 year 1980 , is not yet working effectively. Due to the obstacle factors that affect the effectiveness of the role of the Surakarta City Social Service, namely the absence of a halfway house for homeless people and beggars in order to develop their personalities to be a  better person, so can reduce the number of beggars in the city of Surakarta. Lack of cooperation between agencies such as the Social Service and Satpol PP. In addition, there is no Surakarta City regulation regarding efforts and sanctions for homeless people and beggars.